L’açaí en France d'Outre-Mer : La Guyane française vers une nouvelle frontière agricole de l'Euterpe oleracea dans l'Amazonie septentrionale - Francisco Cortezzi (Confins, 2021)
Originating from the palm Euterpe oleracea, the açaí is an endemic fruit of the Amazon rainforest, the consumption of which has grown strongly in Brazil since the 1990s and is emerging in other regions of the world. Consumed mainly in the form of pulp and erected as a "superfruit" by marketing players for its antioxidant and nutritional potential, the açaí berry goes through a dynamic process encompassing both its space production and international distribution circuit as well as its composition derivative products. With more than 85% of its territory inserted in the Amazon rainforest, French Guiana has all the environmental requirements necessary for the development and production of açaí berries. Currently in this territory, the highest concentration of extractive production of Euterpe oleracea is found in the region of Lower Oyapock, on the border with Brazil. Despite the little government interest behind the fruit, a little over six years ago, agricultural producers in the metropolitan region of Cayenne have closely analyzed the dynamics and consumption of açaí by-products in Europe and on d 'other continents. From the favorable results of the international market analysis, these farmers created the company Yana Wassaï whose main objective is to develop the local production process targeting the foreign market. One of the objectives of this group is to transform the açaí berry into a “European” product. With a large part of the project already underway, the group plans to increase the cultivated area by around 300 hectares in the next three years to reach a total of more than 1,000 hectares of crops in the next eight years. During our stay in French Guiana, it was possible to discuss more closely with the main actors of this project, in addition to visiting and knowing the first irrigated plantations of the palm Euterpe oleracea belonging to the group.